Effect of seeding time on the formation of gold nanoplates - Morsin, Marlia; Mat Salleh, Muhamad; Sahdan, Mohd Zainizan; Mahmud, Farhanahani (Penerbit UTHM, 2017)
Metallic nanostructures, such as gold, is very sensitive to the dielectric environment of the materials due to strong dependency of plasmon on shapes and sizes. Thus, its unique properties are very good and can be used as sensing material in plasmonic sensor. This paper reports a study on the surface density on the formation of gold nanoplates with variation of seeding time. The gold nanoplates have been grown on a quartz substrate using seed mediated growth method. In this study, the seeding time was varied from one to three hours and labelled as MP1, MP2 and MP3. The XRD analysis shows two peaks of the diffraction angle occurs at the plane (111) in position ~ 38.2º and plane (200) at ~ 44.20º. Through variation of the seeding time, the optimum surface density is 61.8 % with a total of 43.7 % of the nanoplates shape from sample MP2. The optical absorption spectrum of the sample shows two resonance peaks, ~ 550 nm and 660 nm, which are corresponding to the transverse surface plasmon resonance (t-SPR) and the longitudinal surface plasmon resonance (l-SPR) respectively. Thus, in this study, it is found that the seeding time affected the growth of the gold nanostructures with optimum seeding time of two hours. Longer seeding time caused the growth of stacking nanogold and it is not suitable to be used in sensing application because of its broad and wider optical spectrum.